Miasto permanentnej migracji. Koncepcja aerotropolii Johna Kasardy i jej społeczne implikacje - Skoczylas, Łukasz (Człowiek i Społeczeństwo, 2020)
This paper presents the concept of the city-airport (aerotropolis) by John Kasarda. This concept is shown in the background of the development of air transport, the creation of large airport hubs and the contemporary processes of globalization. The article describes the advantages and disadvantages of the aerotropolis and shows the compounds of this concept with other theories of new forms of settlement and urbanism. The article presents the probable identity problems that may result from the creation of the city-airport. The text also discusses the chances of the creation of the aerotropolis in Poland.